Green solvent approach for printable large deformation thermoplastic elastomer based piezoresistive sensors and their suitability for biomedical applications - Gonçalves, B. F. (2016)
Composites based on biocompatible thermoplastic elastomer styrene-ethylene/butylene-styrene (SEBS) as matrix and multi-walled carbon nanotubes (MWCNT) as nanofillers show excellent mechanical and piezoresistive properties from low to large deformations. The MWCNT/SEBS composites have been prepared following a green solvent approach, to extend their range of applicability to biomedical applications. The obtained composites with 2, 4 and 5 wt% MWCNT content provide suitable piezoresistive response up to 80% deformation with a piezoresistive sensibility near 2.7, depending on the applied strain and MWCNT content. Composite sensors were also developed by spray and screen printing and integrated with an electronic data acquisition system with RF communication. The possibility to accurately control the composites properties and performance by varying MWCNT content, viscosity and mechanical properties of the polymer matrix, shows the large potential of the system for the development of large deformation printable piezoresistive sensors.